Literacy for all students : an instructional framework for closing the gap - Powell, Rebecca, 1949-; Rightmyer, Elizabeth C. (New York : Routledge, 2011)
"The Culturally Responsive Instruction Observation Protocol (CRIOP) is a framework for implementing culturally relevant literacy instruction and classroom observation. Drawing on research and theory reflecting a range of perspectives on multicultural instruction, literacy theory, equity pedagogy, language and discourse models, sheltered instruction, and critical pedagogy, it provides a means for assessing the many variables of classroom literacy instruction and for guiding practitioners in their development as multicultural educators. Literacy for All Students discusses issues in multicultural literacy instruction within the context of various essential instructional components (such as assessment, curriculum, parent collaboration). Provides a protocol for observing features of literacy instruction for culturally and linguistically diverse students. Presents vignettes from real classrooms, written by elementary and middle school teachers, showing their victories and struggles as they attempt to implement a pedagogy that is culturally responsive within a climate of high stakes testing. A highly effective instrument for assessing culturally responsive literacy instruction in schools, the CRIOP serves as a model for realizing a literacy that is both relevant and transformative"-- Provided by publisher.
"The Culturally Responsive Instruction Observation Protocol (CRIOP) is a framework for implementing culturally relevant literacy instruction and classroom observation. Drawing on research and theory reflecting a range of perspectives on multicultural instruction, literacy theory, equity pedagogy, language and discourse models, sheltered instruction, and critical pedagogy, it provides a means for assessing the many variables of classroom literacy instruction and for guiding practitioners in their development as multicultural educators. Literacy for All Students discusses issues in multicultural literacy instruction within the context of various essential instructional components (such as assessment, curriculum, parent collaboration). Provides a protocol for observing features of literacy instruction for culturally and linguistically diverse students. Presents vignettes from real classrooms, written by elementary and middle school teachers, showing their victories and struggles as they attempt to implement a pedagogy that is culturally responsive within a climate of high stakes testing. A highly effective instrument for assessing culturally responsive literacy instruction in schools, the CRIOP serves as a model for realizing a literacy that is both relevant and transformative"-- Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Language arts teachers -- Rating of -- United States; Multicultural education -- United States; Literacy -- Social aspects -- United States; Language arts -- Social aspects -- United States; Electronic books